A photo-tunable membrane based on inter-particle crosslinking for decreasing diffusion rates1. Issue 7 (21st February 2015) - Li, Song; Moosa, Basem A.; Chen, Ye; Li, Wengang; Khashab, Niveen M.
<x xml:space="preserve">Abstract</x> Functional polymeric membranes are efficiently used to adjust and control the diffusion of molecules.